2022
DOI: 10.3390/ma15144818
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of AZ91 Rein-Forced with High Volume Fraction of Oriented Short Carbon Fibers

Abstract: In this study, AZ91/23 vol.% short carbon fiber composite was produced by a squeeze casting technique using a cylindrical pre-form of treated carbon fibers, in which the fibers are randomly oriented in the horizontal plane. Cylindrical specimens (height = 9 mm and diameter = 6 mm) were machined from the as-cast AZ91 matrix and its composite. The full behavior of the produced composite was studied through the test specimens machined in two directions, namely parallel to the reinforced plane (in the radial direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This arrangement makes the loading of the test specimens parallel to the reinforced plane to have a strengthening effect. Previous studies on AZ91-C [ 14 , 30 ] indicated that the achieved compressive strength [ 30 ] and wear resistance [ 14 ] were lower for samples loaded normal to the reinforced plane (parallel to the cylindrical cast part axis) than that for specimens loaded parallel to the reinforced plane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This arrangement makes the loading of the test specimens parallel to the reinforced plane to have a strengthening effect. Previous studies on AZ91-C [ 14 , 30 ] indicated that the achieved compressive strength [ 30 ] and wear resistance [ 14 ] were lower for samples loaded normal to the reinforced plane (parallel to the cylindrical cast part axis) than that for specimens loaded parallel to the reinforced plane.…”
Section: Resultsmentioning
confidence: 99%
“…The squeeze cast composite was solidified at a rapid cooling rate, reaching around 28.2 °C s −1 . More detailed information about this squeeze casting production technique can be found in the following descriptions [ 14 , 30 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, few points with lower oxygen at.-% have a Cu-Zn ratio that corresponds to the stoichiometry of the β phase of brass. 56,57 After etching, the uppermost layer still has increased amounts of zinc and oxygen (see Figure 2c and Table 1). However, the chemical modification is only observed for ∼100 nm from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Not only that, there are other methods that are also usually undertaken to enhance the mechanical properties of magnesium alloys, namely by adding reinforcing materials to magnesium alloys to make magnesium alloy-based composites in order to upgrade their mechanical properties as required. Referring to several studies that have been conducted previously, incorporating reinforcement materials into magnesium alloys in the form of SiO 2 nanoparticles [ 13 ], carbon nanotubes/CNTs [ 14 ], and short fibers of Al 2 O 3 [ 15 ] or carbon [ 16 ] can considerably improve their mechanical strength [ 15 , 17 ] and creep resistance [ 18 ]. Indeed, short carbon fiber reinforcement has the advantages of increasing stiffness, elastic modulus, and creep resistance while maintaining a light weight, opening up opportunities to expand its use in different engineering applications [ 19 ].…”
Section: Introductionmentioning
confidence: 99%